Noval Teaching Technologies of Pragmatic Speech Acts - Sadikov Erkin Tursunovich (Genius Publishing Group, 2022)
This paper aims to illustrate how to teach speech acts under the umbrella of pragmatics in the EFL classroom. It highlights the significance of pragmatics in raising learners’ local and global linguistic and cultural behaviors. It also opposes to those researchers who claim that learning the foreign language is commonly associated with the vocabulary, grammar and lexical features.
Keywords: Pragmatics; Speech Acts; Culture; Refusals